Qur’anic Literacy for Children: A Community Service Project in Gunung Melayu Asahan - Husin Saidy Sasa (Rahis Cendekia Indonesia, 2024)
This paper presents the implementation and outcomes of a community service project aimed at improving Qur’anic literacy among children in the village of Gunung Melayu, Asahan, North Sumatra. The project was initiated in response to the limited access to structured Qur’anic education in the area, particularly among children aged 6 to 12 years. Using a participatory, community-based approach, the program combined formal instruction in Qur’anic reading and tajwid with interactive and engaging activities. The results showed a significant improvement in the children’s ability to recognize Arabic letters, recite short surahs, and follow basic reading rules. The project also fostered greater parental involvement and communal responsibility for religious education. Despite challenges such as limited teaching resources and facilitators, the initiative proved to be effective and well-received by the community. This project serves as a model for similar efforts in rural or underserved regions, demonstrating how local collaboration